Application of haplotype pair analysis for the identification of hemizygous loci. Issue 5 (1st May 2003) - Hendrickson, B C; Pruss, D; Lyon, E; Scholl, T
Abstract : An expectation maximisation based prediction algorithm was created to identify unusual haplotypes in patient samples that may be caused by small intragenic deletions. In this approach, unphased SNP genotypes are compared to pairs of canonical haplotypes to identify potentially hemizygous regions. This method was successfully applied to identify five deletions in the 3′ region of BRCA1 .